Understanding the correlations between wealth, poverty and human immunodeficiency virus infection in African countries - Justin O Parkhurst (The World Health Organization, 2010)
OBJECTIVE: To investigate the relationships between the prevalence of human immunodeficiency virus (HIV) infection and underlying structural factors of poverty and wealth in several African countries. METHODS: A retrospective ecological comparison and trend analysis was conducted by reviewing data from demographic and health surveys, acquired immunodeficiency syndrome (AIDS) indicator surveys and national sero-behavioural surveys in 12 sub-Saharan African countries with different estimated national incomes. Published survey reports were included in the analysis if they contained HIV testing data and wealth quintile rankings. Trends in the relation between gender-specific HIV prevalence and household wealth quintile were determined with the X² test and compared across the 12 countries, and also within one country (the United Republic of Tanzania) at two points in time. FINDINGS: The relationship between the prevalence of HIV infection and household wealth quintile did not show consistent trends in all countries. In particular, rates of HIV infection in higher-income countries did not increase with wealth. Tanzanian data further illustrate that the relationship between wealth and HIV infection can change over time in a given setting, with declining prevalence in wealthy groups occurring simultaneously with increasing prevalence in poorer women. CONCLUSION: Both wealth and poverty can lead to potentially risky or protective behaviours. To develop better-targeted HIV prevention interventions, the HIV community must recognize the multiple ways in which underlying structural factors can manifest themselves as risk in different settings and at different times. Context-specific risks should be the targets of HIV prevention initiatives tailored to local factors.